Peran Peer Pressure dan Keahlian sebagai Mediator Hubungan Antara Etnis dan Niat Beli - Thania, Thania (APPS Publications, 2021)
The objective of this study is to investigate the roles of peer pressure and expertise as mediating variables on the relationship between ethnicity and intention to purchase. To develop a quantitative strategy, the author employed Smart-PLS to check the hypotheses based on the data from 350 Instagram users of college students aged 18-25 in Jakarta. The results showed that both mediation effects were significant as well as the direct influence of ethnicity towards purchase intention. However, the direct effect of ethnicity towards purchase intention was the most powerful determinant among the relationships. This study considers a particular ethnicity as influencers and their impact to college students’ perspective in purchase intention.